A modified nano cryptocrystalline graphite powder, preparation method thereof and application thereof in rubber

By using surface modifiers and chelating agents in the preparation of crypto-crystalline graphite powder, the problems of poor dispersion and insufficient binding force in the rubber matrix are solved, and the performance improvement of the rubber composite is achieved.

CN116535878BActive Publication Date: 2025-03-28CHINA UNIV OF MINING & TECH (BEIJING)
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310480288.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-28
Publication Date
2025-03-28
Estimated Expiration
2043-04-28

AI Technical Summary

Technical Problem

The prior art is difficult to prepare nano-scale cryptocrystalline graphite powder, resulting in poor dispersion and insufficient binding force in the rubber matrix, affecting the mechanical properties of the rubber composite.

Method used

By initially grinding the cryptocrystalline graphite raw material and preparing it into a slurry with water, adding a surface modifier for grinding and peeling, then adding a chelating agent for stirring, filtering, washing, dehydration and drying, a modified nanocrystalline graphite powder with an average diameter of 100-900 nanometers and a specific surface area of ​​5-40 m2/g was prepared.

Benefits of technology

The efficient preparation of nano-scale cryptocrystalline graphite powder is achieved, the dispersion and binding force in the rubber matrix is ​​improved, and the mechanical and physical properties of the rubber composite are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116535878B_ABST
    Figure CN116535878B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of chemical industry and materials, and specifically relates to a modified nanometer cryptocrystalline graphite powder, a preparation method thereof and its application in rubber. The modified nanometer cryptocrystalline graphite powder has an average diameter of 100 to 900 nanometers, an average thickness of 5 to 50 nanometers, and a specific surface area of ​​5 to 40 m 2 / g. The preparation method comprises: 1) grinding cryptocrystalline graphite raw material preliminarily and adding it into water to prepare cryptocrystalline graphite slurry; 2) adding surface modifier into the prepared cryptocrystalline graphite slurry and grinding to obtain grinding slurry; 3) adding chelating agent into the grinding slurry and stirring, filtering, washing, dehydrating and drying the stirred slurry to obtain. The nano cryptocrystalline graphite prepared by the present invention has small particle size, is not easy to agglomerate, can provide active sites for combining with rubber, has low cost and simple steps, can be used for large-scale industrial production, and fully improves various performances of rubber composites.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of chemical industry and materials, and in particular relates to a modified nano cryptocrystalline graphite powder, a preparation method thereof and application thereof in rubber. Background Art

[0002] Cryptocrystalline graphite is a black earthy mineral with a crystal diameter generally less than 1 μm and a specific surface area ranging from 1 to 5 m 2 / g, it is a collection of microcrystalline graphite. The crystals can only be seen under an electron microscope. The color is gray-black, the luster is dull, and the ore is dense, blocky, earthy, layered and flake-like. The grade of natural cryptocrystalline graphite ore is generally higher than that of flake graphite, but the selectivity of the ore is poor.

[0003] Cryptocrystalline graphite has low crystallization degree and small grains, so its performance is generally inferior to that of flake graphite and its application range is relatively small. At present, it is mainly used as a carburizer in iron and steel making, and in the manufacture of pencil leads. my country has abundant cryptocrystalline graphite resources, but due to the low level of deep processing of products, the advantages of mineral resources have not been fully utilized, resulting in a large amount of resource waste. If deep processing research on cryptocrystalline graphite can be carried out to improve the application range of cryptocrystalline graphite, it will produce huge social and economic benefits.

[0004] Studies have shown that cryptocrystalline graphite, as a two-dimensional layered mineral, has attracted much attention in recent years due to its advantages such as small particle size, easy peeling (interlayer bonding force is only weak van der Waals force), large specific surface area, good electrical and thermal conductivity, environmental protection, pollution-free, and low price. Because it has a similar chemical composition to carbon black, it is similar to carbon black in microstructure, hardness, high conductivity, and stability in oxygen-free corrosive media, making it possible to partially replace carbon black in polymers. Cryptocrystalline graphite particles are very small, with a particle diameter of micrometers, which is difficult to achieve even by grinding ordinary silicate minerals. The small particle size makes it easier to disperse in the rubber matrix, which is beneficial to improving the performance of rubber products. Therefore, using natural cryptocrystalline graphite as a rubber filler has great advantages, low cost, and green environmental protection.

[0005] For example, “Preparation and properties of modified cryptocrystalline graphite / carbon black / nitrile rubber composite materials” discloses a method of using liquid nitrile rubber (LNBR) to modify cryptocrystalline graphite, and then mixing it with carbon black, NBR, etc. to prepare modified cryptocrystalline graphite / carbon black / nitrile rubber composite materials.

[0006] At present, the preparation of cryptocrystalline graphite / rubber composites in my country is mainly developing in the direction of ultrafine grinding, organic modification and graphene preparation. The ultrafine grinding methods of cryptocrystalline graphite minerals are mainly divided into dry grinding and wet grinding. Dry ultrafine grinding mainly uses mechanical impact and high-speed airflow grinding, but its grinding only relies on the collision of the particles themselves, the degree of grinding is low, and secondary agglomeration is very likely to occur after grinding, so the dry grinding effect has certain limitations. Wet grinding uses grinding media to assist in grinding and peeling. Compared with dry grinding, the particle size after wet grinding is smaller, but in industrial wet grinding production, the particle size is usually between 1 and 5μm, and there are no reports of nano-scale cryptocrystalline graphite products.

[0007] Therefore, there are still some problems in the preparation of cryptocrystalline graphite / rubber composites, such as: 1) after normal wet stripping, the minerals have a certain tendency to agglomerate, so the obtained mineral particle size is still large; 2) the bonding force between cryptocrystalline graphite and rubber is only based on van der Waals force, so the interfacial bonding force is weak, and then it is easy to form filler agglomerates, which is not conducive to improving the mechanical properties of the rubber composite and building a filler network.

[0008] In summary, how to obtain nano-scale cryptocrystalline graphite, modify and process cryptocrystalline graphite, improve its dispersion in the rubber matrix, and the interaction between it and the rubber matrix need to be further resolved. Summary of the invention

[0009] The purpose of the present invention is to provide a modified nano-cryptocrystalline graphite powder, a preparation method thereof and application thereof in rubber, aiming to provide a nano-level cryptocrystalline graphite powder to solve the problems that the existing cryptocrystalline graphite has large particle size, is easy to agglomerate, cannot form a good dispersion in the rubber matrix, and has a weak bonding force with the rubber matrix.

[0010] To achieve the purpose of the present invention, the present invention adopts the following technical solution:

[0011] A modified nanometer cryptocrystalline graphite powder, wherein the modified nanometer cryptocrystalline graphite powder has an average diameter of 100 to 900 nanometers, an average thickness of 5 to 50 nanometers, and a specific surface area of ​​5 to 40 m 2 / g.

[0012] The present invention also provides a method for preparing the modified nano cryptocrystalline graphite powder, wherein the preparation method comprises the following steps:

[0013] 1) Preliminarily grinding the cryptocrystalline graphite raw material and adding it into water to prepare cryptocrystalline graphite slurry;

[0014] 2) adding a surface modifier to the prepared cryptocrystalline graphite slurry, and performing grinding to obtain a grinded slurry;

[0015] 3) adding a chelating agent to the slurry after grinding and stirring, and filtering, washing, dehydrating and drying the stirred slurry to obtain the modified nano cryptocrystalline graphite powder.

[0016] The invention uses cryptocrystalline graphite as a raw material, firstly prepares a slurry of a certain concentration, then adds a proper amount of a surface modifier for grinding, utilizes the π-π conjugation effect between the surface modifier and the cryptocrystalline graphite to increase the surface hydrophilicity of the cryptocrystalline graphite and its dispersibility in water, and then prevents its graphite flake structure from forming agglomerates, and then adds a chelating agent for stirring, filtering, washing, dehydrating and drying, and finally obtains highly dispersed modified nano cryptocrystalline graphite powder.

[0017] At the same time, in the present invention, by adding a surface modifier and a chelating agent, not only can the cryptocrystalline graphite be exfoliated better and finer, thereby preparing a nano-level cryptocrystalline graphite powder, but also the interface bonding force between the filler and the rubber can be increased, and its dispersibility in the rubber matrix can be improved to prevent agglomeration, thereby increasing its physical and mechanical reinforcement performance.

[0018] Furthermore, in step 1), the cryptocrystalline graphite raw material is natural cryptocrystalline graphite with different graphitization degrees, preferably natural cryptocrystalline graphite with high graphitization degree of 50%<DOG<100%, 0<FWHM(002)<3.

[0019] In the present invention, DOG is the degree of graphitization, and FWHM (002) is the half-maximum width of the (002) peak on the graphite XRD curve.

[0020] Furthermore, in step 1), the mass concentration of the prepared cryptocrystalline graphite slurry is 5-20%.

[0021] Furthermore, in step 2), the grinding and peeling is carried out by stirring and peeling with a grinding and peeling machine, and the stirring speed is 1000-2350 rpm, the reaction temperature is 20-60° C., and the stirring time is 1-3 hours.

[0022] Furthermore, in step 2), the surface modifier is one or more of polyvinyl pyrrolidone, sodium carboxymethyl cellulose, lignin sulfonate or carboxylate type polymer surfactant, and the added amount is 1-3% of the mass of the cryptocrystalline graphite raw material.

[0023] In the present invention, the purpose of adding the surface modifier is to cover the polar hydrophilic groups on the graphite surface to increase its water solubility and provide active sites for improving the filler-rubber matrix interface force.

[0024] In the present invention, the lignin sulfonate is sodium lignin sulfonate or calcium lignin sulfonate; the carboxylate type polymer surfactant is sodium lignin carboxylate or dodecyl glyceryl ether carboxylate.

[0025] Furthermore, in step 3), the chelating agent is one or more of aminocarboxylates or organic phosphates, and the amount added is 1-3% of the mass of the cryptocrystalline graphite raw material.

[0026] In the present invention, the aminocarboxylate is sodium nitrilotriacetate; and the organic phosphate is aminotrimethylene phosphate.

[0027] Furthermore, in step 3), the stirring speed is 1000-1500 rpm, and the stirring time is 0.5-1 hour; the washing is to wash the filtration solution to a pH value of 6-8; the drying is carried out by drying at a temperature of 100-150° C. for 12-72 hours.

[0028] The invention also provides application of the modified nano cryptocrystalline graphite powder in preparing rubber.

[0029] Specifically, the application is to use the modified nanometer cryptocrystalline graphite powder as filler and melt-blend it with rubber to prepare a nanometer graphite / rubber composite.

[0030] In the present invention, the surface of the modified nano-cryptocrystalline graphite powder used as filler is modified during the preparation process to increase hydrophilic groups, which can serve as active sites, thereby increasing the interface bonding force between the filler and the rubber matrix.

[0031] In the present invention, the rubber is any rubber commonly used in the art, including but not limited to styrene-butadiene rubber.

[0032] Compared with the prior art, the present invention has the following advantages:

[0033] (1) The modified nano-cryptocrystalline graphite powder prepared by adding a surface modifier provided by the present invention requires simple equipment and process, has low production cost, and is highly environmentally friendly, and can be widely used in industrial production;

[0034] (2) Compared with the existing nano-cryptocrystalline graphite production technology, the nano-cryptocrystalline graphite produced by the method of the present invention has a small particle size, is not easy to agglomerate, can provide active sites for bonding with rubber, has low cost, simple steps, can be used for large-scale industrial production, and fully improves various aspects of the performance of the rubber compound;

[0035] (3) The modified nano-cryptocrystalline graphite powder provided by the present invention can be used to prepare nano-graphite / rubber composites, which can improve the mechanical, physical, wear-resistant, air-tight, and electrical and thermal conductivity properties of the rubber composites;

[0036] (4) When the modified nano-cryptocrystalline graphite powder provided by the present invention is used to prepare the nano-cryptocrystalline graphite / rubber composite, the dispersibility of the cryptocrystalline graphite in the rubber matrix is ​​improved, and the filler network structure and the bonding force between the filler and the rubber matrix are constructed. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is a SEM image of the modified nano-cryptocrystalline graphite powder prepared in Example 1 of the present invention;

[0038] Figure 2 This is a SEM image of the unmodified nano-cryptocrystalline graphite powder prepared in Comparative Example 3;

[0039] Figure 3 TEM image of the modified nano-cryptocrystalline graphite / rubber slice prepared in Example 1 of the present invention;

[0040] Figure 4 TEM image of the unmodified nano-cryptocrystalline graphite / rubber slice prepared in Comparative Example 3; DETAILED DESCRIPTION

[0041] The following are specific embodiments of the present invention, and the embodiments are intended to further describe the present invention rather than to limit the present invention.

[0042] Example 1

[0043] 1) selecting cryptocrystalline graphite with high graphitization degree of DOG=83.72% and FWHM(002)=0.49 in the igneous rock intrusion environment as raw material, weighing 150g of the ground cryptocrystalline graphite after preliminary grinding and adding it into 1500ml of water to prepare cryptocrystalline graphite slurry with a mass concentration of 10%;

[0044] 2) adding 1.5 g of surface modifier sodium carboxymethyl cellulose to the prepared cryptocrystalline graphite slurry, and stirring and peeling in a mill at a stirring speed of 2350 rpm, a reaction temperature of 40° C., and a stirring time of 1 hour to obtain a milled slurry;

[0045] 3) Add 1.5 g of chelating agent sodium nitrilotriacetate to the milled slurry, stir at 1000 rpm for 1 hour, filter, wash and dehydrate on a vacuum filter after stirring until the pH value of the filtrate reaches 6 to 8; then dry at 120° C. for 24 hours to obtain modified nano cryptocrystalline graphite powder.

[0046] The modified nano-cryptocrystalline graphite powder obtained in this embodiment has an average diameter of 600 nanometers, an average thickness of 30 nanometers, and a specific surface area of ​​36.04 m 2 / g, its SEM is Figure 1 shown.

[0047] Example 2

[0048] In this embodiment, nano cryptocrystalline graphite is prepared from high-graphitization cryptocrystalline graphite (DOG=80.23, FWHM=0.563) generated by igneous rocks invading coal seams in different regions. The preparation method and process are similar to those in Example 1, except that the surface modifier used in step 2) is sodium lignin sulfonate. The obtained nano cryptocrystalline graphite ore is similar to the product obtained in the process of Example 1, with an average diameter of 650 nanometers, an average thickness of 25 nanometers, and a specific surface area of ​​35.3 m 2 / g.

[0049] Embodiment 3-8

[0050] The preparation process of the modified nano-cryptocrystalline graphite powder described in Examples 3-8 is described in detail in the form of a list below.

[0051] Table 1. Preparation of nano-cryptocrystalline graphite products

[0052]

[0053]

[0054] Comparative Example 1

[0055] In this embodiment, cryptocrystalline graphite (semi-graphite) with a low degree of graphitization is used as a raw material (DOG=39.77, FWHM(002)=4.703) to prepare nano cryptocrystalline graphite. The preparation method and process are the same as those in Example 1, except that the degree of graphitization is low and it has a partially blocky disordered domain aromatic compound structure. Compared with cryptocrystalline graphite with a high degree of graphitization, this sample is not easy to be peeled off. The modified nano cryptocrystalline graphite powder finally obtained has an average diameter of 1.25 μm, an average thickness of 200 nm, and a specific surface area of ​​13.6 m 2 / g.

[0056] Comparative Example 2

[0057] 100 g of the raw material used in Example 1 was crushed in a high-speed crusher at a speed of 2000 rpm for 30 minutes. The obtained product had an average diameter of 2 μm, an average thickness of 500 nm, and a specific surface area of ​​10.4 m 2 Therefore, it is shown that a large number of aggregates still exist when conventional solid phase mechanical crushing method is used.

[0058] Comparative Example 3

[0059] This example refers to Example 1, and the difference from Example 1 is that no surface modifier is added for treatment during the preparation process. The specific steps are as follows:

[0060] 1) selecting cryptocrystalline graphite with high graphitization degree of DOG=77.91% and FWHM(002)=0.502 in the igneous rock intrusion environment as raw material, weighing 150g of the ground cryptocrystalline graphite after preliminary grinding and adding it into 1500ml of water to prepare cryptocrystalline graphite slurry with a mass concentration of 10%;

[0061] 2) Add 1.5 g of chelating agent sodium nitrilotriacetate to the prepared cryptocrystalline graphite slurry, stir at 1000 rpm for 1 hour, filter, wash and dehydrate on a vacuum filter after stirring until the pH value of the filtrate reaches 6 to 8; then dry at 120° C. for 24 hours to obtain modified nano cryptocrystalline graphite powder.

[0062] The modified nano-cryptocrystalline graphite powder obtained in this comparative example has an average diameter of 950 nanometers, an average thickness of 70 nanometers, and a specific surface area of ​​20.02 m 2 / g. Its SEM picture is as follows Figure 2 As shown in the figure, it can be seen that the average diameter and thickness of the filler are relatively large.

[0063] Comparative Example 4

[0064] This example refers to Example 1, and the difference from Example 1 is that no chelating agent is added for treatment during the preparation process. The specific steps are as follows:

[0065] 1) selecting cryptocrystalline graphite with high graphitization degree of DOG=77.91% and FWHM(002)=0.502 in the igneous rock intrusion environment as raw material, weighing 150g of the ground cryptocrystalline graphite after preliminary grinding and adding it into 1500ml of water to prepare cryptocrystalline graphite slurry with a mass concentration of 10%;

[0066] 2) Add 1.5 g of surface modifier sodium carboxymethyl cellulose to the prepared cryptocrystalline graphite slurry, and stir and peel in a mill at a stirring speed of 2350 rpm, a reaction temperature of 40°C, and a stirring time of 2 hours to obtain a milled slurry; filter, wash, and dehydrate the milled slurry on a vacuum filter until the pH value of the filtrate reaches 6 to 8; and then dry at 120°C for 24 hours to obtain modified nano cryptocrystalline graphite powder.

[0067] The modified nano-cryptocrystalline graphite powder obtained in this embodiment has an average diameter of 724 nanometers, an average thickness of 36 nanometers, and a specific surface area of ​​28.27 m 2 / g.

[0068] Application Examples

[0069] The nano cryptocrystalline graphite product prepared by the present invention was used to fill styrene-butadiene rubber and conduct performance reinforcement experiments. The samples made by the comparative example were used as a control group for comparison. The rubber experimental formula is: 100 parts of SBR; 3 parts of zinc oxide; 1 part of stearic acid; 1 part of accelerator; 1.75 parts of sulfur; 50 parts of filler (modified nano cryptocrystalline graphite powder prepared in Examples 1-2 and Comparative Examples 1-4). The experiment used a rotorless vulcanizer, and the vulcanization temperature was 153°C. The tensile tester model is A1-7000GD, and the wear performance is tested using a DIN roller tester. The test results are shown in Table 2 below, Figure 3 TEM image of filler / rubber slice corresponding to Example 1; Figure 4 The filler / rubber slice TEM image corresponding to Comparative Example 3 is shown in FIG. Figure 4 It can be seen that the average diameter and thickness of the filler are relatively large.

[0070] Table 2. Comparative experimental results of styrene-butadiene rubber

[0071]

[0072] The results show (Table 2) that the mechanical and physical properties of the butadiene styrene rubber (SBR) such as tensile strength, tear strength, 100% tensile strength, 300% tensile strength, elongation at break and wear resistance are greatly improved by using the product of the present invention to fill and reinforce the SBR, showing the mutation effect of nanomaterials, and thus having great practical application value. As a comparative example, due to the poor dispersion effect caused by the dry grinding effect, the lack of modifier and chelating agent, the mechanical and physical reinforcement performance of the product is inferior to that of the present invention.

Claims

1. A modified nano-cryptocrystalline graphite powder, characterized in that: The modified nano-cryptocrystalline graphite powder has an average diameter of 100 to 900 nanometers, an average thickness of 5 to 50 nanometers, and a specific surface area of ​​5 to 40 m 2 / g; the modified nano cryptocrystalline graphite powder is prepared by the following method: 1) Preliminarily grinding the cryptocrystalline graphite raw material and adding it into water to prepare cryptocrystalline graphite slurry; 2) adding a surface modifier to the prepared cryptocrystalline graphite slurry, and performing grinding to obtain a grinded slurry; 3) adding a chelating agent to the slurry after grinding and stirring, and filtering, washing, dehydrating and drying the stirred slurry to obtain the modified nano cryptocrystalline graphite powder; In step 2), the grinding and peeling is carried out by stirring and peeling with a grinding and peeling machine, the stirring speed is 1000-2350 rpm, the reaction temperature is 20-60° C., and the stirring time is 1-3 hours.

2. A method for preparing the modified nano-cryptocrystalline graphite powder according to claim 1, characterized in that: The preparation method comprises the following steps: 1) Preliminarily grinding the cryptocrystalline graphite raw material and adding it into water to prepare cryptocrystalline graphite slurry; 2) adding a surface modifier to the prepared cryptocrystalline graphite slurry, and performing grinding to obtain a grinded slurry; 3) adding a chelating agent to the slurry after grinding and stirring, and filtering, washing, dehydrating and drying the stirred slurry to obtain the modified nano cryptocrystalline graphite powder; In step 2), the grinding and peeling is carried out by stirring and peeling with a grinding and peeling machine, the stirring speed is 1000-2350 rpm, the reaction temperature is 20-60° C., and the stirring time is 1-3 hours.

3. The preparation method according to claim 2, characterized in that: In step 1), the cryptocrystalline graphite raw material is natural cryptocrystalline graphite with various degrees of graphitization.

4. The preparation method according to claim 3, characterized in that: In step 1), the cryptocrystalline graphite raw material is natural cryptocrystalline graphite with a high degree of graphitization of 50%<DOG<100%, 0<FWHM(002)<3.

5. The preparation method according to claim 2, characterized in that: In step 1), the mass concentration of the prepared cryptocrystalline graphite slurry is 5-20%.

6. The preparation method according to claim 2, characterized in that: In step 2), the surface modifier is one or more of polyvinyl pyrrolidone, sodium carboxymethyl cellulose, lignin sulfonate or carboxylate type polymer surfactant, and the added amount is 1-3% of the mass of the cryptocrystalline graphite raw material.

7. The preparation method according to claim 2, characterized in that: In step 3), the chelating agent is one or more of aminocarboxylates or organic phosphates, and the added amount thereof is 1-3% of the mass of the cryptocrystalline graphite raw material.

8. The preparation method according to claim 2, characterized in that: In step 3), the stirring speed is 1000-1500 rpm, and the stirring time is 0.5-1 hour; the washing is to wash the filtration solution to a pH value of 6-8; the drying is carried out by drying at a temperature of 100-150° C. for 12-72 hours.

9. Use of the modified nano cryptocrystalline graphite powder according to claim 1 in the preparation of rubber.

10. The use according to claim 9, characterized in that: The application is to use the modified nano cryptocrystalline graphite powder as claimed in claim 1 as filler and melt-blended with rubber to prepare a nano graphite / rubber composite.

Citation Information

Patent Citations

  • Method for preparing small-diameter graphene

    CN103922323A

  • Nano-graphite slurry preparation method

    CN105060281A

  • Microcrystalline graphite filler, sizing material using same, and preparation method and application of sizing material

    CN115895028A